Asymmetric spillovers and connectedness between crude oil and currency markets using high-frequency data. (August 2022) - Mensi, Walid; Shafiullah, Muhammad; Vo, Xuan Vinh; Kang, Sang Hoon
Abstract: This paper examines the asymmetric spillovers and connectedness between the spot prices of West Texas Intermediate crude oil and six popular currencies—the Euro, Japanese Yen, British Pound, Australian Dollar, Swiss Franc, and Canadian Dollar. We analyze the asymmetric realized volatility spillovers spot prices as well as the higher moments such as their realized skewness and kurtosis. The estimated results indicate that these markets are strongly interconnected and that the currencies of larger economies as well as resource exporters are mainly net transmitters of volatility. However, this attribute is time-varying, especially during global economic events/shocks. The asymmetric volatility analysis finds that bad volatilities trump good ones on average. This attribute of the sample markets is also time-varying. The evaluation of directional networks in semi-variances reveals the dominance of bad volatilities over good ones and that bad volatilities from the currencies of larger and resource-based economies and the crude oil market are imparted for the most part. Moreover, the bad volatility of the British Pound, especially in the wake of Brexit, is a key contributor of its good volatility. However, in the wake of the COVID-19 pandemic, currencies of resource-based economies as well as the crude oil appear to impart small magnitudes of good volatilities. These findings have important implications for policymakers and highlight the need for responses tailored to different periods and markets. Highlights: Asymmetric connectedness between crude oil and currency markets is examined. The total spillover of higher moments and jump risk are time-varying. Larger- and resource-exporter economies are net transmitters of volatility. Bad volatilities trump good ones on average. Bad volatilities originate largely from larger and resource-based currencies.